2018
DOI: 10.1039/c7en01245d
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient photothermal sterilization of water mediated by Prussian blue nanocages

Abstract: Photothermal sterilization based on PBNs has been demonstrated not only upon NIR irradiation but also most importantly under simulated solar light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Other literature reported that Prussian blue could kill E. coli 100% within 5 min through the photothermal effect. However, due to its high photothermal conversion rate, Prussian blue may increase the risk of damage to normal tissue ( Jiang et al, 2018 ). Tannic acid is a polyphenolic compound, which is the active ingredient extracted from gallnut ( Ninan et al, 2016 ; Yan et al, 2019 ; Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other literature reported that Prussian blue could kill E. coli 100% within 5 min through the photothermal effect. However, due to its high photothermal conversion rate, Prussian blue may increase the risk of damage to normal tissue ( Jiang et al, 2018 ). Tannic acid is a polyphenolic compound, which is the active ingredient extracted from gallnut ( Ninan et al, 2016 ; Yan et al, 2019 ; Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The optical properties of nanocages were not different, with the usual absorption band centered around All of these papers are oriented towards in vivo applications and to the functionalization of biomedical devices. Yu and colleagues proposed another field of applications for PBNPs, which could have great potential: photothermal sterilization of water [42]. In this case, Prussian blue nanocages were used instead of solid nanoparticles.…”
Section: Photothermal Antibacterial Effect Of Prussian Blue Nanoparticlesmentioning
confidence: 99%
“…The self-assembled monolayers demonstrated photothermally induced antibacterial activity against Gram-negative ( E. coli ) and Gram-positive ( S. aureus ) bacterial strains. In order to overcome the NIR laser limits and to irradiate larger areas, the nanocages were used to induce the photothermal sterilization upon solar light irradiation [ 75 ]. In a very recent article, published in 2019, physically cross-linked PVA hydrogel films, containing Prussian blue nanoparticles, displayed a pronounced photothermal effect (up to Δ T ≅ 78 °C) under low NIR laser intensities (0.3 W/cm 2 ) [ 76 ].…”
Section: Reviewmentioning
confidence: 99%